POLYGAMOUS MARRIAGE REVIEW FROM LAW NUMBER 1 OF 1974 CONCERNING MARRIAGE - Agnes Maria Janni Widyawati; Heri Purnomo (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
In principle, the Marriage Law adheres to the principle of monogamy, but it does not rule out those who wish to polygamy as long as their religion and belief allows and can fulfill the requirements stipulated by the Marriage Law. This is reflected in Article 3 paragraph 1 of the Marriage Law which reads: In principle, in a marriage a man can only have one wife, a woman can only have one husband; The court may give permission for a husband to have more than one wife if the parties wish to do so. Thus it can be seen that the principle of monogamy adopted by the Marriage Law is not absolute.